Perfil sérico das proteínas, metabólitos, minerais e enzimas de bovinos da raça Bonsmara em fase de crescimento, e em vacas lactantes, gestantes e não gestantes - Barbosa, Fernando Cristino (2019)
The introduction and use of taurine breeds in commercial cattle breeding is an important component for improving the efficiency of the beef cattle production system of Brazilian livestock. The Bonsmara breed belongs to a racial group of European origin (Bos taurus taurus), introduced in Brazil in 1997 as a genetic alternative for crossbreeding with Zebu breeds. Serum biochemical profile can be used as an indicator of the body's adaptive processes to nutritional and physiological challenges; specific metabolic imbalances and energy; and protein and mineral metabolisms; and also, physiological variations due to factors such as race, age, gender, pregnancy and lactation. In order to evaluate the influence of age and gender on serum protein, metabolite, mineral and enzyme concentrations in Bonsmara cattle not older than two years of age, blood samples were collected from 179 animals (92 males and 87 females), ranging from 15 days old to 24 months of age, which were separated into four age groups: G1: from 15 days to 2 months, G2: from 2 to 6 months, G3: from 6 to 12 months and G4: from 12 to 24 months. To evaluate the influence of pregnancy and lactation order on serum protein, metabolite, mineral and enzyme concentrations in first, second and third lactation order, blood samples were collected from 93 cows, from which 34, 29 and 30 were first, second and third lactation order, respectively. Samples were processed in a multichannel automated analyzer using Labtest Diagnostics® kits. To compare the values between age groups and lactation orders, the Kruskall-Wallis test was chosen. To compare the values of males and females within each age group and those of pregnant and nonpregnant cows within the lactation orders, the Mann-Whitney test was used. Age significantly influenced the values of most serum biochemical constituents evaluated, except for magnesium (Mg) and Ca+:Pi ratio. Older age imposed an elevation of total proteins (PT), globulins (Glob), urea, creatinine (Crea), aspartate aminotransferase (AST), alanine aminotransferase (ALT) values, but a decrease of cholesterol (COL), calcium (Ca+), inorganic phosphorus (Pi), alkaline phosphatase (FAL) and gamma glutamyltransferase (GGT) values. Gender influenced serum albumin (ALB), Glob, A:G ratio, Crea, urea, triglycerides (TRI), Ca+, Pi, Ca+:Pi ratio and Mg values. The order of lactation significantly influenced only the serum ALB concentration and pregnancy in the value of the A: G ratio for third lactation cows, and in the COL, TRI, Pi, iron (Fe), AST and FAL for second lactation cows of the general group. It was concluded that the variables age and sex influence most of the evaluated serum constituents, and influence of pregnancy and lactation order on the concentration of several serum biochemical constituents of Bonsmara cows, especially in second lactation order cows.